(untitled) (Texas Journal of Medical Science, 2025)
This article provides a comprehensive study of the clinical and immunological characteristics of early childhood epileptic encephalopathy. Within the framework of the research, diagnostic criteria were developed to enable early identification of epileptic encephalopathy and its differential diagnosis from other forms of epilepsy. Immunological markers — interleukin-1 (IL-1), interleukin-10 (IL-10), and tumor necrosis factor-alpha (TNF-α) — and their relationship with clinical manifestations were analyzed. Based on the obtained results, scientific and practical recommendations were developed to improve the effectiveness of early diagnosis and treatment.